(untitled) (Window of Public Health Journal, 2025)
Stunting poses a significant challenge in Indonesia, particularly in Gowa Regency, which ranks fourth highest for stunting cases in South Sulawesi, according to the 2018 Riskesdas data. In Pallangga District specifically, the community’s knowledge about stunting remains low, mainly due to varying levels of education among residents. This study analyzes the relationship between community education levels and knowledge about stunting in the Pekang Labbu Environment of Tetebatu Village, Pallangga District, Gowa Regency, in 2024. Using a quantitative method with a descriptive statistical approach, data were collected through questionnaires completed by 200 respondents. The findings revealed a significant correlation between the level of education and knowledge about stunting; individuals with lower education levels tended to have less understanding of the issue. This study highlights the crucial role of community education in raising awareness and preventing stunting, and it offers recommendations for more targeted health education programs.